Inovasi dalam Pelatihan Keterampilan Komunikasi: Mengoptimalkan Pengalaman Magang Mahasiswa - Wardhani, Nia Kusuma; Variani, Davita; Aini, ⁠Luthfi Noor (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Soft skills are skills related to personality and individual characteristics that are difficult to measure quantitatively. Communication is one of the skills that is very important in the work environment. These skills contribute to creating an open and friendly atmosphere and ensure that the resulting performance is clearer and more focused. Students' inability to build productive communication can hinder the smoothness of the internship process at the practice location. Conflicts between colleagues and human resources can create disharmony in company operations. The Student Creativity Program (PKM) aims to provide training. By obtaining soft skills training in the form of productive communication skills, students are expected to be able to: (1) focus on solutions, not problems; (2) get used to using positive and motivational sentences; (3) focus on the goals to be achieved; and (4) be visionary, with an orientation towards the future rather than the past. The method applied is online training for students participating in the MSIB program. The training implementation consists of three stages: material delivery, training, roleplay, and assessment. The result of this training is more organized material, which ensures students gain in-depth understanding and skills in effective communication. The participants' responses to this coaching and training showed that 100% felt that the training provided motivation and was fun to learn, especially prospective internship students because this training was very effective online.